A Comment on the Term "Positive Behavior Support". (July 2014) - Dunlap, Glen; Kincaid, Donald; Horner, Robert H.; Knoster, Timothy; Bradshaw, Catherine P.
The use of the term "positive behavior support" has been associated with some confusion, and a number of alternative terms have been adopted over the past few decades. In this article, we discuss some of the historical context associated with different terms, and explain reasons for preferring "positive behavior support (PBS)" as the term for referring to the PBS approach.